Flexible wellbeing and organizational creativity: personality traits role - Umukoro, Jones; Egwakhe, Johnson; Akpa, Victoria (Business: Theory and Practice, 2021)
Organizational creativity is indispensable in a highly competitive and dynamic academic environment; and the role of individuals is mostly unquantifiable. Hence the study argued that the ideas, novel research output, patents, grants of the academic staff depend on the flexible wellbeing of the workforce which is at a low level in Nigeria. Thus, the paper investigated the role of personality traits on the relationship between flexible wellbeing and organizational creativity. The paper implemented a cross-sectional survey research design and collated data from six hundred and twenty-one academic staff ranked from Senior Lecturer to Professor from eight selected private universities in South-West, Nigeria through applying multi-stage random sampling technique. Reliable and validated tests were conducted on the adapted questionnaire before it was used for the study. The result from hierarchical regression analysis using SPSS add-on called process analysis revealed that personality traits have a moderating effect on the interactions between flexible wellbeing and organizational creativity (ΔR2 = 0.014, ΔF(1, 528) = 13.579, p < 0.05). Management to tailor wellbeing policies and practices to workers’ creative drive as there is no “one-size-fits-all” approach to designing an effective flexible wellbeing strategy.